A new interpretation of components in the ERG signals to sine wave luminance stimuli at different temporal frequencies and contrasts - Pangeni, Gobinda; Horn, Folkert; Kremers, Jan (Visual Neuroscience, 2010)
Full-field electroretinograms were recorded from five normal human subjects using white light (mean luminance: 250 cd/m(2)) sine wave stimuli at different frequencies and contrasts. In agreement with previous studies, we found that the amplitude of the fundamental component displayed a dip at about 12 Hz, coinciding with a maximum in the second harmonic component, indicating frequency doubling of the responses. By including measurements at different contrasts, we were able to recognize two (sine-like and transient) response components. We found that the waveform of the transient response was relatively frequency independent. An algorithm to separate the two components was developed. The interaction between these two components can explain the frequency-doubled responses around 12 Hz. The sine-like component is more linear and prominent in the low-frequency region, whereas the transient seems to be more nonlinear and prominent in the high-frequency region.
Keywords: Electroretinogram; Sine wave stimuli; Component analysis; Temporal modulation; Luminance contrast